(untitled) (Pakistan Journal of Engineering, Technology and Science, 2024)
This comprehensive review examines the link between AI and software development by examining their interplay throughout all development life cycle stages. The research combines insights from current literature and industry practices, to shed light on AI’s impact on processes such as requirement analysis, design, coding, and testing. The study uses the Review Paper technique for examination, covering a wide range of sources, including academic databases, research portals, and publications. The seven-week timeframe includes data analysis, a study of the literature, and a critical examination of the implications and effective role of AI. The study indicates that AI is a collaborative tool in software development, based on historical and contemporary technical realities. The study not only gives more detailed knowledge but also establishes the framework for future research. underlining the need for industry-specific AI applications and a better evaluation of developers’ experiences. This research acts as a guidepost for industry executives and academics, providing insights into the changing landscape influenced by AI on software development